Assessment of Metro Vancouver Canada Immigration Consulting Firm’s Existing Strategies: Basis for Business Resiliency Strategic Plan During Canadian Border Closures - Abrera, Noel Almonte (Digital Repository of Theses - SSBM Geneva, 2024)
The proposed research aims to determine the effectiveness of different Marketing Strategies being used by Metro Vancouver Canada Immigration Consulting regarding business resiliency during Canadian border closures which influence the company’s intention in aiming to develop strategic policies in order to have a precise business resiliency and strategies during Canadian border closures while continuing business operations. Specifically, to assess the effectiveness of the research approach, Data analysis, survey research, management and staff interviews were among the research approaches employed in the study. The findings demonstrated that the company's present strategy was primarily focused on providing clients with excellent immigration services, fostering lifelong relationships with stakeholders to enhance its operations. This study's findings stress the importance of assessing current strategies to identify any potential weaknesses and opportunities for business resilience in the face of unforeseen challenges like border closures. The firm can adjust to the shifting business environment and keep offering its clients high-quality services by putting the suggested tactics into practice.